Tinjuan Teologi Kepemimpinan Berhati Hamba Menurut Filipi 2:1-11 Bagi Pembentukan Karakter Jemaat - Paulus Kunto Baskoro (Sekolah Agama Kristen Terpadu Pesat Salatiga, 2021)
Leadership is very important. Leadership will grealty affect all aspects of the movement in God’s church. Good leadership will produce an extraornidary movement, but if leadership is not good, it will bring decline in a church. God gives trust to church leaders to bring every church to be more advanced and fruitful for the Kingdom of God. Leadership also affects the character of the congreation. God longs for every congregation in God’s church to have a Christ-like character. But the problem that arises in a leadership is when someone gets trusted to lead in a church, tends to be authoritarian and arbitratry. Do not base leadership with a servant’s heart. The context of this discussion is focused on the example of Jesus in Philippians 2:1-11 who truly has the character of a servant’s heart ministry in the world. This research uses a descriptive literature method, which is to learn about the Theological Review of Servant Leadership According to Philippians 2:1-11 For Congregational Character Building from the point of view of the truth of God’s Word, because the Bible is the standard of life for believers. The aim is that trough this writing, First, servant-hearted leadership becomes the lifestyle of every Christian leader. Second, Christian leaders can impart a good example to every believer according to the example of Jesus. Third, the character of the congregation is getting better. Fourth, God’s church grows to the maximum and can produce futher spiritual leaders who have a servant’s heart.AbstrakKepemimpinan adalah hal yang sangat penting. Kepemimpinan akan sangat mempengaruhi seluruh aspek kegerakan dalam gereja Tuhan. Kepemimpinan yang baik akan menghasilkan sebuah gerakan yang luar biasa, namun jika kepemimpinan tidak baik, maka akan membawa kemunduran dalam sebuah gereja. Tuhan memberikan kepercayaan kepada para pemimpin gereja untuk membawa setiap gereja menjadi makin lebih maju dan berbuah bagi Kerajaan Allah. Kepemimpinan juga memengaruhi karakter jemaat. Tuhan merindukan setiap jemaat yang ada dalam gereja Tuhan memiliki karakter yang seperti Kristus. Namun problem yang muncul dalam dalam sebuah kepemimpinan adalah ketika seseorang mendapat kepercayaan memimpin dalam sebuah gereja, cenderung otoriter dan semena-mena. Tidak mendasarkan kepemimpinan dengan hati hamba. Konteks pembahasan ini difokuskan kepada teladan Yesus dalam Filipi 2:1-11 yang sungguh memiliki karakter hati hamba dalam pelayanan di dunia. Penelitian ini menggunakan metode diskritif literatur, yaitu mempelajari tentang pribadi Tinjauan Teologis Kepemimpinan Berhati Hamba Menurut Filipi 2:1-11 Bagi Pembentukan Karakter Jemaat dari sudut pandang kebenaran Firman Tuhan, sebab Alkitab adalah standart kehidupan orang percaya. Tujuannya supaya lewat penulisan ini yaitu Pertama, kepemimpinan berhati hamba menjadi gaya hidup setiap pemimpin Kristen. Kedua, pemimpin Kristen dapat mengimpartasikan teladan yang baik bagi setiap orang percaya sesuai dengan teladan Yesus. Ketiga, karakter jemaat menjadi lebih baik. Keempat, gereja Tuhan bertumbuh dengan maksimal dan bisa memunculkan pemimpin-pemimpin rohani selanjutnya yang memiliki hati hamba.